2002
DOI: 10.1002/syn.10088
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin modulation of cerebral glucose metabolism measured with positron emission tomography (PET) in human subjects

Abstract: To develop a method to measure the dynamic response of the serotonin system in vivo, the effects of intravenously administered citalopram (the most selective of the serotonin reuptake inhibitors) on cerebral glucose metabolism were evaluated. Cerebral glucose metabolism was measured with positron emission tomography (PET) in 14 normal subjects scanned after administration of saline placebo and citalopram administered on 2 separate days. Citalopram administration resulted in a decrease in metabolism in the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 57 publications
7
47
0
Order By: Relevance
“…The following LDAEP measurements were performed 10, 30 and 60 min after the infusion had ended. Recording was arranged at these times as neuroendocrinological studies showed that the main effect on the central serotonergic system is to be expected during or right after the infusion (Seifritz et al, 1996;Kapitany et al, 1999;Smith et al, 2002). At the end of each testing day, BDI questionnaire had to be answered once more.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following LDAEP measurements were performed 10, 30 and 60 min after the infusion had ended. Recording was arranged at these times as neuroendocrinological studies showed that the main effect on the central serotonergic system is to be expected during or right after the infusion (Seifritz et al, 1996;Kapitany et al, 1999;Smith et al, 2002). At the end of each testing day, BDI questionnaire had to be answered once more.…”
Section: Methodsmentioning
confidence: 99%
“…enhancement of serotonin in the synapses by reuptake inhibition (Sanchez and Hyttel, 1999). It is known that the intravenous administration of citalopram leads to significant neuroendocrinological changes of prolactin, cortisol, and growth hormone immediately after infusion (Seifritz et al, 1996;Smith et al, 2002). Furthermore, experiments with in vivo microdialysis showed that citalopram produces an enormous increase of serotonin immediately after injection (Bosker et al, 2001;Muraki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, an alternative approach has been developed to measure serotonin function in vivo by combining the administration of citalopram with positron emission tomography (PET) measurements of cerebral glucose metabolism (Smith et al, 2002b). The initial studies in healthy controls demonstrated that the intravenous administration of citalopram resulted in steady-state plasma concentrations of citalopram for up to 3 h after the end of infusion and time-dependent increases in cortisol and prolactin levels.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroendocrine (prolactin and cortisol) and cerebral glucose metabolic responses to acute citalopram administration were evaluated as described previously (Smith et al, 2002b). Based on previous basic and clinical research with 5-HTTLPR, it was hypothesized that because the s allele is associated with lower serotonin function, the s allele would be associated with less of a neuroendocrine and metabolic response compared to the l allele.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have focused on the development and application of a method to measure serotonin function in vivo (Meyer et al, 1999;Hume et al, 2001;Smith et al, 1999Smith et al, , 2002bSmith et al, , 2004. Studies conducted thus far in geriatric depression combining acute and chronic SSRI treatment (citalopram) with measures of cerebral glucose metabolism have shown a differential lateralized pattern of acute metabolic effects in the patients in contrast to comparison subjects that are similar to the response in normal subjects who have a s allele of the serotonin transporter promoter polymorphism compared to those normal subjects with a l allele (Smith et al, 2004).…”
Section: Neurochemical Imaging Approachesmentioning
confidence: 99%